Legal - Political Analysis of Indigenous Relocation in Rempang : Between Agrarian Justice and the Shadow of Colonial Land Doctrine. (Study Of Land Tenure Conflict Between The Community And BP Batam) - Mustafa, Ilham; Suhadi, Suhadi; Irawaty, Irawaty (Journal of Law, Politic and Humanities, 2025)
The agrarian conflict in Rempang Island emerged due to the planned relocation of the indigenous Kampung Tua Rempang community by the Batam Development Authority (BP Batam) for development of Rempang Eco City, designated as National Strategic Project (PSN). The community rejected relocation, arguing that they have inhabited the land for generations prior to the establishment of the Batam Authority, despite lacking formal land ownership certificates. This study aims to : analyze the government's legal policy regarding relocation and assess whether the Rempang case reflects the colonial-era principle of Domein Verklaring, which treats land without proof of ownership as state property. This research uses a normative juridical approach, focusing on analysis of laws and regulations such as Basic Agrarian Law (UUPA) No. 5 of 1960, Presidential Decree No. 41 of 1973, Presidential Decree No. 28 of 1992, and Government Regulation No. 18 of 2021. The findings reveal that BP Batam lacks legal standing, as Land Management Rights (HPL) certificate for Rempang has not been issued, and legal requirements such as compensation, community consultation, and relocation have not been fulfilled. This relocation practice closely resembles Domein Verklaring and represents form of modern agrarian colonialism that contradicts principles of justice in Indonesia’s agrarian law.